Ethical considerations in sexual health research: A narrative review - Maryam Shirmohammadi; Shahnaz Kohan; Ehsan Shamsi-Gooshki; Mohsen Shahriari (Wolters Kluwer Medknow Publications, 2018)
Background: There is an assumption that sexual health research has great influence on the quality of human life through elevating sexual health standards, and their results will eliminate the burden of sexual health challenges on family relationships. The aim of this study was to review ethical considerations in sexual health research. Materials and Methods: This narrative review was conducted between January 1990 and December 2017 based on the five-step approach of York University. The keywords used to search for the studies included ethical issues, research, sexual health, reproductive health, and sensitive topics. The language of the literatures was English and the search process was performed on PubMed, Elsevier, Ovid, Springer, Google Scholar, ResearchGate, SAGE Publishing, ProQuest, WHO website, Kinsey Confidential, and Worldsexology. Results: After assessing the quality and eligibility of 94 articles, 13 were selected. The results of the present study showed that the most important ethical considerations were protecting the confidentiality and privacy of participants, obtaining informed consent, and paying attention to vulnerable people. Conclusions: The review of literature exhibited several considerations that sexual health researchers are faced with. In order to manage these considerations, the researcher should have sufficient understanding of them. The important matter is that strategies to manage these challenges should be completely rational and practical according to each context. These strategies can also be applied in other societies with great similarities in their context.